Commodification of knowledge in system of higher education; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Pankova N. M. Nataliya Mikhailovna (2017, 2017)
Title screen